Overcoming the Obstacles Faced by Early Career Researchers in Marine Science: Lessons From the Marine Ecosystem Assessment for the Southern Ocean - Brasier, Madeleine J.; McCormack, Stacey; Bax, Narissa; Caccavo, Jilda A.; Cavan, Emma; Ericson, Jessica A.; Figuerola, Blanca; Hancock, Alyce; Halfter, Svenja; Hellessey, Nicole; Höfer, Juan; Puskic, Peter S.; et al. (Frontiers in Marine Science, 2020)
Pressure in academia and science is rapidly increasing and early career researchers (ECRs) have a lot to gain from being involved in research initiatives such as large international projects. But just how inclusive are they? Here we discuss experiences of ECRs directly involved in the Marine Ecosystem Assessment for the Southern Ocean (MEASO), an Australian led international research project to assess the status and trends of Southern Ocean ecosystems. We review the benefits of ECR involvement in large-scale initiatives to the project deliverables, the leadership team and ECRs themselves. Using insights from MEASO, we outline the obstacles that may become barriers to ECRs in scientific research in general an more particularly in large-scale research projects across different disciplines and suggest potential actions to overcome these at the individual, institutional and scientific community level. We consider the potential for ECRs to lead future Antarctic science programmes with a focus on science communication and applied research for policy makers within a global setting.